2005
DOI: 10.1002/ejic.200500515
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Complexes Containing Chiral N‐Donor Ligands as Catalysts in Acetophenone Hydrogen Transfer – New Amino Effect on Enantioselectivity

Abstract: New p-cymene ruthenium species containing chiral amino alcohols (1-3), primary (4-7) and secondary (8, 9) aminooxazolines, were tested as catalysts in the hydrogen transfer of acetophenone, using 2-propanol as the hydrogen source. A remarkable effect on the enantioselectivity, but also on the activity, was observed depending on the amino-type oxazoline, Ru/8 and Ru/9 being low active and nonselective catalytic systems, in contrast to their primary counterpart Ru/5. Complexes containing amino-oxazolines (10-12)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The first step for the synthesis of 1,2,3-benzotriazinones was the preparation of 2-(o-aminophenyl)oxazolines 3a-3c (see (1)). These oxazolines were prepared in high yields (58-80%) by cyclization of anthranilonitrile with ethanolamines under basic conditions in a mixture of glycerol and ethylene glycol, following the methodology reported by Gómez and coworkers [19]. In the literature, it has been reported that oxazolines 3a and 3b were obtained as oils, whereas in our work both were isolated as solids; we believe this fact is due to problems in the purification process in the previous report.…”
Section: Resultsmentioning
confidence: 54%
“…The first step for the synthesis of 1,2,3-benzotriazinones was the preparation of 2-(o-aminophenyl)oxazolines 3a-3c (see (1)). These oxazolines were prepared in high yields (58-80%) by cyclization of anthranilonitrile with ethanolamines under basic conditions in a mixture of glycerol and ethylene glycol, following the methodology reported by Gómez and coworkers [19]. In the literature, it has been reported that oxazolines 3a and 3b were obtained as oils, whereas in our work both were isolated as solids; we believe this fact is due to problems in the purification process in the previous report.…”
Section: Resultsmentioning
confidence: 54%
“…33,34 Formation of the compounds containing Ru-H from Ru-Cl precursors are well-documented 35 such as in situ generated Ru-H species can act as the active catalysts for transfer hydrogenation of ketones. [36][37][38] The proposed mechanism of transfer hydrogenation of ketone using catalysts reported in the manuscript is depicted in Scheme 4.…”
Section: Scheme 1 Synthesis Of N-substituted Imidazoline and Benzimimentioning
confidence: 99%